Fine-Tuning of Alkaline Residues on the Hydrophilic Face Provides a Non-toxic Cationic α-Helical Antimicrobial Peptide Against Antibiotic-Resistant ESKAPE Pathogens - Luo, Xudong; Ye, Xiangdong; Ding, Li; Zhu, Wen; Yi, Pengcheng; Zhao, Zhiwen; Gao, Huanhuan; Shu, Zhan; Li, Shan; Sang, Ming; Wang, Jue; Zhong, Weihua; et al. (Frontiers in Microbiology, 2021)
Antibiotic-resistant ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) has become a serious threat to public health worldwide. Cationic α-helical antimicrobial peptides (CαAMPs) have attracted much attention as promising solutions in post-antibiotic era. However, strong hemolytic activity and in vivo inefficacy have hindered their pharmaceutical development. Here, we attempt to address these obstacles by investigating BmKn2 and BmKn2-7, two scorpion-derived CαAMPs with the same hydrophobic face and a distinct hydrophilic face. Through structural comparison, mutant design and functional analyses, we found that while keeping the hydrophobic face unchanged, increasing the number of alkaline residues (i.e., Lys + Arg residues) on the hydrophilic face of BmKn2 reduces the hemolytic activity and broadens the antimicrobial spectrum. Strikingly, when keeping the total number of alkaline residues constant, increasing the number of Lys residues on the hydrophilic face of BmKn2-7 significantly reduces the hemolytic activity but does not influence the antimicrobial activity. BmKn2-7K, a mutant of BmKn2-7 in which all of the Arg residues on the hydrophilic face were replaced with Lys, showed the lowest hemolytic activity and potent antimicrobial activity against antibiotic-resistant ESKAPE pathogens. Moreover, in vivo experiments indicate that BmKn2-7K displays potent antimicrobial efficacy against both the penicillin-resistant S. aureus and the carbapenem- and multidrug-resistant A. baumannii, and is non-toxic at the antimicrobial dosages. Taken together, our work highlights the significant functional disparity of Lys vs Arg in the scorpion-derived antimicrobial peptide BmKn2-7, and provides a promising lead molecule for drug development against ESKAPE pathogens.